Diterpenes Synthesized from the Natural Serrulatane Leubethanol and Their in Vitro Activities against Mycobacterium tuberculosis - Escarcena, Ricardo; Pérez Meseguer, Jonathan; Del Olmo, Esther; Alanís Garza, Blanca Alicia; Garza González, Elvira; Salazar Aranda, Ricardo; Waksman de Torres, Noemí (2015)
Seventeen new derivatives of the natural diterpene leubethanol, including some potential pro-drugs, with changes in the functionality of the aliphatic chain or modifications of aromatic ring and the phenolic group, were synthesized and tested in vitro by the MABA technique for their activity against the H37Rv strain of Mycobacterium tuberculosis. Some compounds showed antimycobacterial selectivity indices higher than leubethanol.